The Role of the Village Government in Improving Public Services for the Keboansikep Village Community - Choiriyah, Ilmi; Mursyidah, Lailul; Sukmana, Hendra; Agustina, Isna (Indonesian Journal Publisher, 2021)
The aim of this research is to analyze and describe the role of the village government in improving public services in the Keboansikep village community, in order to find out the problems in improving services through the role of government. The approach taken in this research is a qualitative descriptive approach by conducting interviews, observation and documentation. The data analysis model according to Miles and Huberman (1992) uses data collection techniques, data reduction, data presentation and drawing conclusions. The results of this research show that, firstly, the objectives implemented by archiving management in Keboansikep Village are trying to provide better public services for the people in Keboansikep village so that they can easily access the information needed such as population documents, birth certificates and other important documents. Second, this IT training was carried out to help increase the capacity of human resources in Keboansikep village in managing information technology in order to increase the accessibility of information to the community easily. Through the creation of sustainable village website content, positive changes can occur in the dynamics of village communication and development, towards a more advanced, connected and inclusive direction. Third, the use of social media services which can provide many benefits for the community and village government agencies in achieving goals. program. With the existence of social media services such as Instagram, it can be used to introduce the advantages of villages to the wider community